CASE BASED REASONING PENYAKIT ITIK PETELUR MENGGUNAKAN ALGORITMA SIMILARITAS SORGENFREI K-N-N - Yudanto Wibisono; Dwiati Wismarini (LPPM STMIK Lombok, 2021)
Livestock is a fairly large industry in Indonesia. One of the livestock that is quite widely developed in Indonesia is laying ducks. Laying ducks are one of the poultry that are managed to produce quality eggs. However, the laying duck industry often experiences problems in its maintenance process. One of the causes is a disease that is difficult to guess and difficult to get a cure, so that many ducks die or fail to harvest. To deal with this, a technological innovation is needed that can identify the symptoms of the disease experienced by ducks and also a solution for handling the disease. So that ducks can be saved from diseases that cause death or crop failure. Case-Based Reasoning (CBR) is defined as a methodology for solving problems by utilizing experience. Case Based Reasoning (CBR) can assist farmers in identifying diseases based on the symptoms experienced by livestock. This system can be applied with the KNN sorgenfrei similarity algorithm, namely by matching the symptoms of the disease experienced by ducks with other symptoms that have been previously encountered. So, breeders get a conclusion about the disease experienced by ducks and can take appropriate solution steps so that the laying ducks do not die. Keywords : Case-Based Reasoning (CBR), Similaritan KNN Sorgenfreen, laying ducks. Livestock is a fairly large industry in Indonesia. One of the livestock that is quite widely developed in Indonesia is laying ducks. Laying ducks are one of the poultry that are managed to produce quality eggs. However, the laying duck industry often experiences problems in its maintenance process. One of the causes is a disease that is difficult to guess and difficult to get a cure, so that many ducks die or fail to harvest. To deal with this, a technological innovation is needed that can identify the symptoms of the disease experienced by ducks and also a solution for handling the disease. So that ducks can be saved from diseases that cause death or crop failure. Case-Based Reasoning (CBR) is defined as a methodology for solving problems by utilizing experience. Case Based Reasoning (CBR) can assist farmers in identifying diseases based on the symptoms experienced by livestock. This system can be applied with the KNN sorgenfrei similarity algorithm, namely by matching the symptoms of the disease experienced by ducks with other symptoms that have been previously encountered. So, breeders get a conclusion about the disease experienced by ducks and can take appropriate solution steps so that the laying ducks do not die.